Evaluasi Kontrol Kualitas Pemeriksaan Glukosa Darah di Laboratorium X Palangka Raya: Evaluation of Quality Control of Blood Glucose Examination in Laboratory X Palangka Raya - Ferina Yudita; Dwi Purbayanti; Fitria Hariati Ramdhani; Eka Jaya (Borneo Journal of Medical Laboratory Technology, 2023)
Quality Control is a managerial procedure to adjust the laboratory examination (analytic) stages and detect errors early. The purpose of this study was to describe the quality control in laboratory X in the city of Palangka Raya. The method used is the descriptive method. The results showed that in April 2022, the Mean (88,1 mg/dL), SD (1,09 mg/dL), CV (1,24%), d (0,14%), TE (2,62%), TEa (10%), Sigma (7,94), and in May 2022 the Mean (87,9 mg/dL), SD (1,00 mg/dL), CV (1,13%), d (0,04%), TE (2,31%), TEa (10%), Sigma (8,79). According to the Ministry of Health, the maximum CV value is < 5%, so the inspection results of control materials in April 2022 and May 2022 are good or thorough. The maximum d value according to ISO 15179 is < 5%, so the inspection results of control materials in April 2022 and May 2022 are good or accurate. The evaluation of the control material with the Levey Jennings chart showed that all values in April 2022 and May 2022 were within the control limits, and none were outside the limits of the Westgard Mulrirule System rules. The result shows that the internal quality control activities of clinical chemistry for glucose parameters in Laboratory X are well executed and reliable.